(untitled) (Tempo e Argumento, 2012)
The text deals with the role of political propaganda at television in the History teaching and learning process, through the processes of ransom and reinforcement of symbols and ideas referred to the Brazil’s political history, targeted to the building of power projects. This is, therefore, a study that aims to contribute to the knowledge of relationship between formal and informal aspects of History teaching and learning. It begins by the theoretical basis of the History Didactics that gets on the historical consciousness its main concept (cf. J. Rüsen, K. Jeissman, P. Seixas and others). The methodology consists, beyond the tools of televising messages analysis (mainly R. Barthes), at the identification and analysis of the narratives and / or “ultra-short histories” that exists in the political speech that can activate elements of the imaginary and collective memory in immediate objectives’ duty. The preliminary conclusion is that teaching-learning and media messages joins a same circle of relationship, and understand it is mean understanding the interdependence and domination games between these spheres.